The Brussels Infant and Toddler Stool Scale: A Study on Interobserver Reliability. Issue 2 (February 2019) - Huysentruyt, Koen; Koppen, Ilan; Benninga, Marc; Cattaert, Tom; Cheng, Jiqiu; De Geyter, Charlotte; Faure, Christophe; Gottrand, Frédéric; Hegar, Badriul; Hojsak, Iva; Miqdady, Mohamad; Osatakul, Seksit; et al.
ABSTRACT: Objectives: The Bristol Stool Form Scale (BSFS) is inadequate for non-toilet trained children. The Brussels Infant and Toddler Stool Scale (BITSS) was developed, consisting of 7 photographs of diapers containing stools of infants and toddlers. We aimed to evaluate interobserver reliability of stool consistency assessment among parents, nurses, and medical doctors (MDs) using the BITSS. Methods: In this multicenter cross-sectional study (2016–2017), BITSS photographs were rated according to the BSFS. The reliability of the BITSS was evaluated using the overall proportion of perfect agreement and the linearly weighted κ statistic. Results: A total of 2462 observers participated: 1181 parents (48.0%), 624 nurses (25.3%), and 657 MDs (26.7%). The best-performing BITSS photographs corresponded with BSFS type 7 (87.5%) and type 4 (87.6%), followed by the BITSS photographs representing BSFS type 6 (75.0%), BSFS type 5 (68.0%), BSFS type 1 (64.8%), and BSFS type 3 (64.6%). The weakest performing BITSS photograph corresponded with BSFS type 2 (49.7%). The overall weighted κ-value was 0.72 (95% CI 0.59–0.85; good agreement). Based on these results, photographs were categorized per stool group as hard (BSFS type 1–3), formed (BSFS type 4), loose (BSFS types 5 and 6), or watery (BSFS type 7) stools. According to this new categorization system, correct allocation for each photograph ranged from 83 to 96% (average: 90%). The overall proportion of correct allocations was 72.8%. Conclusions: BITSS showed good agreement with BSFS. Using the newly categorized BITSS photographs, the BITSS is reliable for the assessment of stools of non-toilet trained children in clinical practice and research. A multilanguage translated version of the BITSS can be downloaded athttps://bitss-stoolscale.com/ . Abstract : Supplemental Digital Content is available in the text